2011
DOI: 10.1016/j.pnpbp.2011.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Zolpidem reduces the blood oxygen level-dependent signal during visual system stimulation

Abstract: Zolpidem is a short-acting imidazopyridine hypnotic that binds at the benzodiazepine binding site on specific GABAA receptors to enhance fast inhibitory neurotransmission. The behavioral and receptor pharmacology of zolpidem has been studied extensively, but little is known about its neuronal substrates in vivo. In the present within-subject, double-blind, and placebo-controlled study, blood oxygen level-dependent functional magnetic resonance imaging (BOLD fMRI) at 3 Tesla was used to assess the effects of zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Instead the connectivity may reflect some aberrant state that occurs at the expense of task-related function. Our data support this notion since here we show that visual RSNs exhibited increased connectivity, while previously we reported that in these same participants zolpidem reduced BOLD activation during visual stimulation (Licata et al, 2011a). Similarly, acute challenge with alcohol increased resting state correlations in a visual RSN (Esposito et al, 2010) while prior to that it had been shown to reduce BOLD signal activation in visual cortical areas during presentation of a stimulus (Levin et al, 1998; Calhoun et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Instead the connectivity may reflect some aberrant state that occurs at the expense of task-related function. Our data support this notion since here we show that visual RSNs exhibited increased connectivity, while previously we reported that in these same participants zolpidem reduced BOLD activation during visual stimulation (Licata et al, 2011a). Similarly, acute challenge with alcohol increased resting state correlations in a visual RSN (Esposito et al, 2010) while prior to that it had been shown to reduce BOLD signal activation in visual cortical areas during presentation of a stimulus (Levin et al, 1998; Calhoun et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…All scanning sessions began at 10:30 am. The resting state scan preceded a passive visual stimulation scan as well as a key press task scan, both of which were reported on previously (Licata et al, 2011a). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study investigating the relation of baseline GABA concentration as measured by MRS and the fMRI response in visual cortex [27] found that the signal variations of the BOLD contrast are linked to baseline GABA levels in a significant negative correlation, associating higher BOLD signal changes with lower GABA levels and vice versa. Results from a study investigating the effects of Zolpidem, a drug enhancing GABAergic inhibition, on visual response to a checkerboard pattern [28] point into the same direction, linking GABA-mediated inhibition and reduced BOLD responses. GABA receptors as the major inhibitory neurotransmitter receptors are found abundantly in the cortex.…”
Section: Discussionmentioning
confidence: 91%
“…Most hypnotics are benzodiazepine receptor agonists known to impair various aspects of cognition (Barker et al, ; Vermeeren, ). Benzodiazepine receptors are widely distributed throughout the brain (McCabe & Wamsley, ; Zezula, Cortes, Probst, & Palacios, ), and previous fMRI and PET studies have demonstrated that benzodiazepine receptor agonists inhibit neuronal activities involved in separate cognitive tasks (Licata et al, ; Mintzer et al, ). The results of an electroencephalogram study demonstrated that low doses of triazolam, similar to those used in the present study, can cause cortical dysfunction (Urata et al, ).…”
Section: Discussionmentioning
confidence: 99%